A Polymorphism of the Corticotropin-Releasing Hormone Receptor 2 (CRHR2) and Preterm Birth. Issue 1 (2nd June 2013) - Schmid, Maximilian; Grimm, Christoph; Leipold, Heinz; Knöfler, Martin; Haslinger, Peter; Egarter, Christian
Abstract : Our aim was to investigate whether a genetic variation in the corticotropin-releasing hormone receptor 2 gene might be associated with preterm birth. In this case-control study we evaluated the G/A polymorphism (rs2267717) in intron 2 of the corticotropin-releasing hormone receptor 2 gene in one hundred women with preterm birth and one hundred healthy women with at least one uncomplicated full term pregnancy and no history of preterm birth. No significant correlation was found between the presence of the investigated polymorphism and preterm birth ( p = 0.9, odds ratio 0.9 [Confidence interval 0.5–1.7]). A dose dependent association of the investigated polymorphism, in women with preterm birth, with gestational age at delivery ( p = 0.003) and birth weight was observed ( p = 0.0001). However, no association between IUGR ( n =10) with either one of the investigated genotypes ( p = 0.3) was found. Stratified analysis within case group (i.e. PPROM vs. non-PPROM) revealed no significant difference in genotype distribution ( p = 0.6). In conclusion, the investigated polymorphism does not increase the risk for preterm birth overall but might modulate the length of pregnancy in a dose dependent fashion in a series of Caucasian women.